New treatment options for lupus – a focus on belimumab - Chiche L; Jourde N; Thomas G; Bardin N; Bornet C; Darque A; Mancini J (Dove Medical Press, 2012)
Laurent Chiche1,2, Noémie Jourde3, Guillemette Thomas1, Nathalie Bardin2, Charleric Bornet4, Albert Darque4, Julien Mancini51Department of Internal Medicine, Centre de Compétence Maladies Auto-immunes Systémiques PACA Ouest, 2Laboratory of Immunology, 3Department of Nephrology, 4Department of Pharmacy, Hôpital de la Conception, Marseille; 5Department of Public Health, Hôpital de la Timone, Marseille, FranceAbstract: Belimumab is the first biologic approved for patients with systemic lupus erythematosus (SLE). Belimumab is the first of a new class of drug targeting B cell-stimulating factors or their receptors to reach the market. Its target, BLyS, also known as BAFF (B cell-activating factor from the tumor necrosis factor family), is a type II transmembrane protein that exists in both membrane-bound and soluble forms. Additionally to a robust rational from murine experiments conducted in lupus prone mice, BLyS circulating levels are increased in SLE patients. After the negative results of a Phase II trial, two Phase III trials met their primary endpoints. Some SLE patients are still refractory to the standard options of care or necessitate prolonged high-dose corticotherapy and/or long-term immunosuppressive regimens. However, some experts still feel that the effect of this biologic might not be clinically relevant and blame the use of the new systemic lupus response index as well as the discrepancies between both trials and the noninclusion of the severe form of the disease as nephritis. In this review, we aim to discuss the characteristics of belimumab, critically evaluate the different steps of its development, and consider its future place in the arsenal against SLE, taking into account the patients’ perspectives.Keywords: systemic lupus erythematosus, belimumab, treatment, monoclonal antibodies, adverse effects, BLyS